Evidence-based management strategies in infusion therapy: an expanded approach (Research, Society and Development, 2022)
Infusion Therapy has been disseminated and improved in countries that seek a high standard of quality in health. Studies show that institutions seek care excellence using quality management strategies that improve existing activities, achieving results at the care, economic, bureaucratic and administrative level. The study aimed to describe multimodal strategies from the perspective of patient safety in the use of vascular access, demonstrating its benefits through evidence-based practice for the management and strengthening of Organizational Communication. The results proved to be promising from the perspective of several countries and institutions regarding the positive impact that they overcome barriers promoting a change both in the patient safety culture and in institutional policy. The development of health professionals, effective communication and patient experience were highlighted in this research. The study proposes a reflection on the need for the engagement of the entire organization to implement Infusion Therapy more effectively and encourages further research based on a broader look at the subject.